Clinical benefits of therapeutic hypothermia after in-hospital cardiac arrest with surface cooling method in Phyathai 2 Hospital: Two cases report - Muengtaweepongsa, Sombat; Thamrongwang, Teera; Hampromrach, Suchada (The Bangkok Medical Journal, 2012)
Therapeutic hypothermia is a standard recommended treatment for patients after out-of-hospital cardiac arrest. However, clinical benefits of therapeutic hypothermia for patients with in-hospital cardiac arrest have not yet been approved. The present report aims to demonstrate clinical benefit of therapeutic hypothermia in patients with in-hospital cardiac arrest at the Phyathai 2 Hospital.